TINDAK TUTUR EKSPRESIF SIMPATI BELASUNGKAWA PADA MASYARAKAT JEPANG - Rahayu, Umi Fithri; Aibonotika, Arza; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to compare types of condolence speech in Japanese society to the different speech partners and describe the relationship between the situation and the speech form. The research performed for this report used the qualitative-descriptive method and Hiroshi Kabaya’s theory of “aite reberu” and “kotoba reberu”, the theory of words level based on the partner level. 140 samples of data have been collected by using an open questionnaire, and the respondents were twenty Japanese native speakers. The result of this research shows that there are twenty-eight types of Japanese condolence speech. It was also discovered that in expressing this way of speech, the use of kotoba reberu (words level) is not always the same level with aite reberu (partner level). It is influenced by the situation of speech. Some data show that if “aite reberu” is a close friend, it does not necessarily have to use futsuutai, but keigo can also be used in condolence speech sentence and futsuutai be used in the following sentences. In this case, keigo function is to express formal feeling, respect, and compassion.Keywords: condolence, sympathy, expressive, speech act